POST TRAUMATIC TETANUS AND ROLE OF MAGNESIUM SULPHATE - Sikendar, Rana Imran; Samad, Bader us; Ali, Safdar; Memon, Mohammad Iqbal (Journal of Ayub Medical College Abbottabad, 2009)
Background: Tetanus is a life threatening disease. Reported mortality for tetanus is 15-39%. Conventional treatment includes heavy sedation and artificial ventilation. Complications resulting from long term heavy sedation and artificial ventilation contribute to 60% of the total mortality caused by tetanus. In this study magnesium sulphate was used to reduce the need for sedation and artificial ventilation. Objectives of this prospective study were to determine the role of magnesium sulphate in post traumatic tetanus. Methods: The study was carried out in surgical Intensive Care at Pakistan Institute of Medical Sciences (PIMS), Islamabad from Jan 2004 to Dec 2007. Forty-four patients presented during this period and 33 patients were included in the study. All patients had tracheostomy done within 48 hours. Every patient was started Magnesium Sulphate therapy for control of spasms after sending baseline investigations. Patients were given ventilatory support when needed. All data was entered in well structured proforma. SPSS-10 was used to analyse data. Results: Thirty-three patients were included in the study and all patients were given magnesium sulphate. Out of these, 45.5% cases were grade 4 tetanus, 73.6% and 63.3% cases did not require artificial ventilation and additional sedation respectively, 51.1% patients remained free of complications of tetanus. Overall mortality was 30.3%. Conclusions: Use of Magnesium Sulphate is safe and reduces the need for sedation and artificial ventilation in high grade tetanus thus contributing to survival benefit in adult post-traumatic tetanus cases. Keywords: Post traumatic tetanus, artificial ventilation, Magnesium Sulphate